Interactive media based on project-based learning using Lumi Education for IPAS subjects in 4th-grade elementary school - Zikkrillah Nur Miftakhul Laili Yulia; Triwahyudianto Triwahyudianto; Farida Nur Kumala; Wan Muhammad Aiman (Education and Development Research, 2025)
This research is motivated by the needs of fourth-grade students of SDN 5 Pandesari who tend to be passive and have low learning motivation, thus affecting the achievement of IPAS learning. The purpose of this study is to describe the development process, determine the validity, practicality, and effectiveness of PjBL-based interactive media using the Lumi Education application. This type of research is Research and Development (R&D) which uses the ADDIE development model as the basis for product development. The results in this study indicate that PjBL-based interactive media using the Lumi Education application: 1) valid for use in IPAS learning with a percentage of 96% from media experts with the category